The Triple Helix Theory as a Solution for the Unification of the Hijri Calendar in Indonesia - Fitriyanti, Vivit; Haries, Akhmad; Syakur, Abd (Al-Fikrah, 2024)
The Islamic calendar system is an important element of Islamic civilization, but its uniform implementation across the Muslim world, including Indonesia, remains a challenge. Despite Indonesia's Muslim majority, differences persist in determining the start and end of months in the Hijri calendar. Various efforts to establish a unified Islamic calendar have not yet succeeded. This study, titled "The Triple Helix Theory as a Solution for the Unification of the Hijri Calendar in Indonesia," aims to explore Muslim perceptions regarding this unification and examine the role of the government using the Triple Helix theory. The research employs a mixed-method approach, combining quantitative and qualitative methods. The findings show that 77.44% of respondents believe the unification of the Hijri calendar is necessary, while 22.6% do not. Additionally, the study reveals that the Triple Helix theory can be applied as follows: (1) The government, particularly the Ministry of Religious Affairs, should act as a regulator and facilitator; (2) Academics should provide scholarly input consistent with Islamic principles; and (3) Islamic organizations should issue fatwas that unify Muslims in Indonesia, as their decisions are highly influential within the community.